Preliminary analysis of waves in the coastal zone of Monte Hermoso and Pehuén Co, Argentina - Delgado, Ana Laura (2012)
Coastal geomorphology is significantly influenced by waves because they are a major agent in removing and transporting sediments. Furthermore, any kind of human coastal activity is influenced by waves. Consequently, it is essential to know about the wave distribution of the coastal areas. The aim of this study was to analyze the waves at Monte Hermoso and Pehue´n Co coastal zone, Buenos Aires, Argentina. The study was based on data obtained from an oceanographic tower located on the coast of the study area, between April 2007 and July 2009, analyzed annually and seasonally. The major occurrence and frequency of the significant wave heights (Hs) and the period of significant waves (Ts) were studied. The main percentages of Hs occurred between 0.25 and 1.5 m and were related to Ts between 0 and 16 seconds. The highest Hs rates were observed in spring, whereas the lowest ones in winter. Theoretical distribution probabilities were applied and the Weibull distribution was the most appropriate fit for the data, presenting a shape parameter of 0.82 and a scale parameter of 1.73. Joint probability analysis of Hs and Ts showed that summer and spring have similar patterns with larger probabilities of locally generated waves, whereas, contrary to what it is normally expected, winter has the larger percentage of swells because of the large number of calm-wind days. Finally, the Ursell number and the flux intensity parameter were obtained to demonstrate that the waves have been able to transport the typical sediments at the tower site toward the sea.